Poétique de la violence dans le roman algérien contemporain - Leila Moussedek (My University, 2011)
" Poetics of the violence " wants a reflection on five novels establishing(constituting) a model of the contemporary Algerian novel. To seize better this model of writing, our study assigns as task to examine of what consists its originality, its specificity and its peculiarity and to encircle this poetics of the violence through the study of all the techniques and the processes creating the textual violence informer as well as analyzes him(it) aesthetic, thematic models and inter textual arousing this shape of modern writing. The violent act ravaging Algeria of the 90s also ravages the literary text to give substance to him, direct,it and confer him a personality by the language . The violent style succeeds in translating a political and ideological thought which opposes to the terrorism and Islamist fanaticism .
Keywords: Violence-Terrorism-Islamism-Poétic-Rhétoric-imagination-Intertextuality.